2020
DOI: 10.21203/rs.3.rs-84003/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Robotic Versus Laparoscopic Gastrectomy for Gastric Cancer: A Systematic Review and Meta-Analysis

Abstract: Background To date, robotic surgery has been widely used worldwide. We conducted a systematic review and meta-analysis to evaluate short- and long-term outcomes of robotic gastrectomy (RG) in gastric cancer patients to determine whether RG can replace laparoscopic gastrectomy (LG).Methods Pubmed, Cochrane Library, WanFang, China National Knowledge Infrastructure (CNKI) and VIP databases were comprehensively searched for studies published before May 2020 that compared RG with LG. Next, two independent reviewers… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Three previous meta-analyses comparing the perioperative and oncologic outcomes of RG to LG were published (5,6,35). However, the sample size of two meta-analyses was relatively small (6,35), and the study of recurrence-free survival outcome of RG. Compared with their results, our study included some recent studies (27)(28)(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Three previous meta-analyses comparing the perioperative and oncologic outcomes of RG to LG were published (5,6,35). However, the sample size of two meta-analyses was relatively small (6,35), and the study of recurrence-free survival outcome of RG. Compared with their results, our study included some recent studies (27)(28)(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, studies on RG have been broadly reported. Although several meta-analyses have compared the safety and feasibility of RG with LG, these meta-analyses comprised a small sample size, low-quality studies, and no RCT, which limited them to deduce objective conclusions (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, future studies with multicenter collaboration are needed to control for the influence of surgical experience. Besides, future studies should also assess the value of robotic surgery in the era of neoadjuvant chemotherapy for patients with GC [46]. Notably, Li et al showed that after four cycles of neoadjuvant chemotherapy, LG and OG were comparable in terms of distal and proximal margins, number of resected or metastatic lymph nodes, postoperative complications, operative time, blood loss, and length of hospital stay [28].…”
Section: Discussionmentioning
confidence: 99%